Efficacy of knee arthroplasty on the outcomes of knee osteoarthritis in iranian elderly individuals - Roya Hamedi; Parand Pourghane; Roya Mansour-Ghanaei; Zahra Atrkar-Roushan (Wolters Kluwer Medknow Publications, 2021)
Background: Knee osteoarthritis is a common musculoskeletal condition in elderly individuals. This survey was conducted with the aim to identify the problems of this group of patients for compilation of healthcare programs targeted at determining the outcome of osteoarthritis before and 3 months after knee arthroplasty. Materials and Methods: In the present cross-sectional study, 150 elderly individuals who had volunteered for knee arthroplasty were selected through nonrandomized sampling and were evaluated using the Knee Osteoarthritis Outcome Score (KOOS) questionnaire and a demographic characteristics form before and 3 months after the surgery via nonparametric statistical tests (Wilcoxon, Mann-Whitney U, and Kruskal-Wallis tests). Results: The mean (SD) age of the study subjects was 64.40 (7.20) years. A significant difference was observed between the mean scores of all subscales (pain with Z=10.62, knee pain/knee stiffness with Z=10.54, daily activity with Z=10.62, sport with Z=2.95, and quality of life with Z=10.48) before and after knee arthroplasty based on Wilcoxon test (˂0.05). The results of the Mann-Whitney U test showed a significant statistical relationship between the difference in the mean score of daily activities and history of opium consumption (Z=1.90, p ˂ 0.05) as well as that between knee pain/knee stiffness and gender (Z=2.57, p ˂ 0.05) and educational level (Z=2.11, p ˂ 0.05). Conclusions: Knee arthroplasty and history of opium consumption were correlated with improvement of patients' performance in their daily activities, and gender (women) and educational level (unread) were correlated with improvement of the score of the knee pain/knee stiffness subscale.